PENGARUH KETERAMPILAN DASAR MENGAJAR GURU EKONOMI TERHADAP MOTIVASI BELAJAR SISWA KELAS X DI SMA N PANGEAN KABUPATEN KUANTAN SENGINGI - Janprima Ardinsi; Sakdanur Nas; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTMotivation to learn is the mental strength that encourages learning. Motivation can be effective if done with attention to the needs of the students. Thus teachers should equip themselves with various skills that are expected to assist in carrying out its duties in educational interaction. Teaching basic skills is a skill that is an absolute must have in this case the teacher. Teaching the basic skills of the teacher is questioning skills, skills provide reinforcement, keterampila n hold variations, explaining skills, skills to open and close the lesson, the skills to guide small group discussions, classroom management skills, and teaching skills of small group and individual discussions. Ownership is expected to teach basic skills to optimize the role of the teacher in the classroom.The purpose of this study was to determine the effect of teaching the basic skills of teachers and the indicators on student motivation. Research using multiple regression method. Simultaneous testing showed the value of f count test (5.789)> from f table (2.078) at 5% significance basic skills teaching economics teacher influence on student motivation. Partial test showed that the asked basic skill (X1), advanced questioning skill(X2),  provide skill reinforcement(X3), skills to guide small group discussions teaching (X7), skills of small group discussions and individual (X9) had no effect on student motivation (Y) . While other skills, namely: skills held variations  (X4), explaining skills(X5),  opening and closing skills lessons classroom (X6), management skills (X8) effect on student motivation (Y). Keywords: Teaching basic skills, learning Motivation